1997
DOI: 10.1055/s-0038-1655959
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Factor Xa/Phospholipid Infusion on the Acute Phase Response in Baboons

Abstract: SummaryDisseminated intravascular coagulation (DIC) is a frequent complication of septicemia or tissue injury and may be accompanied by elevations of interleukin-6, a mediator of the acute phase response. It is not known whether thrombin or fibrin deposition may directly induce an acute phase response. To study this, we employed a baboon model of in vivo thrombin generation, induced by the administration of purified bovine Factor Xa and phospholipid vesicles. Two Xa/phospholipid dosages were used, a low dosage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…26,27 Further, BIBT 986 infusion significantly and dosedependently reduced the LPS-induced increases in IL-6 and TNF-a in a recent study with rats. Animal studies showed that infusion of factor Xa as well as thrombin infusion increase the production of proinflammatory cytokines such as IL-6.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…26,27 Further, BIBT 986 infusion significantly and dosedependently reduced the LPS-induced increases in IL-6 and TNF-a in a recent study with rats. Animal studies showed that infusion of factor Xa as well as thrombin infusion increase the production of proinflammatory cytokines such as IL-6.…”
mentioning
confidence: 82%
“…Animal studies showed that infusion of factor Xa as well as thrombin infusion increase the production of proinflammatory cytokines such as IL-6. 26,27 Further, BIBT 986 infusion significantly and dosedependently reduced the LPS-induced increases in IL-6 and TNF-a in a recent study with rats. 28 Therefore, we compared the anticoagulant activity of three doses of BIBT 986 on parameters of coagulation, platelet activation, and inflammation with placebo and examined the safety of BIBT 986 in this setting.…”
mentioning
confidence: 82%
“…a. j. chu CD18 174 revealing the initiation of inflammation by TF. The direct evidence includes (i) administration with recombinant FVIIa enhances IL-6 and -8 production in healthy human subjects, 175 (ii) FXa/PL infusion increases L-6 and CRP in baboons, 176 and (iii) FIIa with fibrin(ogen) dependency induces macrophage adhesion and the production of IL-6 and MCP-1.…”
Section: Tf Upregulation Driving a Thrombosis-inflammation Circuit Inmentioning
confidence: 99%
“…The full picture of the clinical tolerance of the injection of FXa/PCPS, as well as the analysis of the parameters illustrating the modifications of the coagulation and fibrinolytic systems in baboons were described in detail previously (3,13,14). No complications were seen after injection of "low dose" FXa/PCPS, but after the first bolus of "high dose" FXa/PCPS all animals presented a transient venous collapse during 30 min which prevented blood collection in this period.…”
Section: The Coagulation System After In Vivo Thrombin Generationmentioning
confidence: 99%